2000
DOI: 10.1007/s001980050286
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Osteoporosis Using Easily Obtainable Biometrical Data: Diagnostic Accuracy of Measured, Self-Reported and Recalled BMI, and Related Costs of Bone Mineral Density Measurements

Abstract: The aims of the present study were: to determine the diagnostic accuracy of objectively measured, self-reported and recalled body mass index (BMI) for osteoporosis and osteopenia; to determine the diagnostic costs, in terms of bone mineral density (BMD) measurements, per osteoporotic or osteopenic patient detected, using different BMI tests; and to determine the extent to which the results can be used within the framework of the current screening program for breast cancer in The Netherlands. Within the framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Prospective studies found that the early postmenopausal women who have low BMI lose more bones compared to those with higher BMI tertiles [4, 8]. In other cross-sectional studies, however, thinness is related to both osteoporosis and increased fracture risk [10, 11]. Iqbal et al [9] found that low BMI is a good indicator for referral of women less than 60 years old for measurements of BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies found that the early postmenopausal women who have low BMI lose more bones compared to those with higher BMI tertiles [4, 8]. In other cross-sectional studies, however, thinness is related to both osteoporosis and increased fracture risk [10, 11]. Iqbal et al [9] found that low BMI is a good indicator for referral of women less than 60 years old for measurements of BMD.…”
Section: Discussionmentioning
confidence: 99%
“…In all, 23 general practitioners (GPs) from 12 GP centres participated in this baseline study 1719. Most (n=21) of these GPs continued to be involved throughout.…”
Section: Methodsmentioning
confidence: 99%
“…A questionnaire enquired about possible risk factors for osteoporosis, which included their medical history (including fracture history), family history and diet 1719. Then, 10 years later, the women who had participated completed a questionnaire about fracture history and medical history.…”
Section: Methodsmentioning
confidence: 99%
“…WHO used astandardized score, called T-score, which compare BMD to average values for young healthy women to define osteoporosis.T-score of -2.5 and below is categorized as osteoporosis 2 .Role of obesity as a risk factor for osteoporosis and its related consequences remains unsettled. Several studieshave reported that body mass index has a positive correlation with BMD, thereby showing a protective role against osteoporosis [3][4][5] . However, there are some studies that contradict to this data [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%